2003
DOI: 10.1084/jem.20021546
|View full text |Cite
|
Sign up to set email alerts
|

CD36 Mediates the Innate Host Response to β-Amyloid

Abstract: Accumulation of inflammatory microglia in Alzheimer's senile plaques is a hallmark of the innate response to β-amyloid fibrils and can initiate and propagate neurodegeneration characteristic of Alzheimer's disease (AD). The molecular mechanism whereby fibrillar β-amyloid activates the inflammatory response has not been elucidated. CD36, a class B scavenger receptor, is expressed on microglia in normal and AD brains and binds to β-amyloid fibrils in vitro. We report here that microglia and macrophages, isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
394
2
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(415 citation statements)
references
References 31 publications
13
394
2
6
Order By: Relevance
“…Both Webster et al (2001) and Das et al (2003) demonstrated A␤ phagocytosis in the presence of immune complexes in vitro; however, this result was only observed with the addition of fucoidan, which acted to block scavenger receptor binding. We and others have demonstrated the requirement for the B-class scavenger receptor CD36 participation in fA␤-stimulated microglia activation (Moore et al, 2002;Bamberger et al, 2003;El Khoury et al, 2003). The present study has established that CD36 is also essential for stimulation of fA␤ phagocytosis by microglia.…”
Section: Discussionsupporting
confidence: 48%
“…Both Webster et al (2001) and Das et al (2003) demonstrated A␤ phagocytosis in the presence of immune complexes in vitro; however, this result was only observed with the addition of fucoidan, which acted to block scavenger receptor binding. We and others have demonstrated the requirement for the B-class scavenger receptor CD36 participation in fA␤-stimulated microglia activation (Moore et al, 2002;Bamberger et al, 2003;El Khoury et al, 2003). The present study has established that CD36 is also essential for stimulation of fA␤ phagocytosis by microglia.…”
Section: Discussionsupporting
confidence: 48%
“…The class B scavenger receptor type 2, CD36, is involved in the Mu response to oxidized LDL [7,27] and mediates microglial and Mu responses to b-amyloid [28]. This scavenger receptor also recognizes anionic phospholipids [8], apoptotic cells [9], thrombospondin [29] and P. falciparum-infected erythrocytes [10].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that A␤ activates NADPH oxidase through the scavenger receptors RAGE (receptor for advanced glycation end product) or CD36 (El Khoury et al, 1996Khoury et al, , 2003Yan et al, 1996;Coraci et al, 2002). Activation of these receptors leads to increased ROS production, which is mediated by NADPH oxidase (Wautier et al, 2001;Bamberger et al, 2003;Abramov et al, 2004;Fuhrman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%